2011
DOI: 10.1007/s00284-011-0050-y
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Curtobacterium Bacterium Promotes Growth of White-Rot Fungus Stereum sp.

Abstract: White-rot basidiomycetes are the main decomposers of woody biomass in forest ecosystems. Little is known, however, about the interactions between white-rot fungi and other microorganisms in decayed wood. A wood-rotting fungus, Stereum sp. strain TN4F, was isolated from a fruit body, and its coexisting cultivable bacteria were isolated from its substrate; natural white-rot decayed wood. The effects of bacteria on fungal growth were examined by confrontational assay in vitro. A growth-promoting bacterium for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Bacterial mycophagy has also been described in different environments (Leveau and Preston, 2008). Under controlled conditions, some bacterial strains have been proven capable of promoting (Kamei et al, 2012;Bontemps et al, 2013) or inhibiting (Radtke et al, 1994) the growth of white-rot fungi. More specifically, from a functional point of view, it has been suggested that bacterial-fungal interactions during the wood decay process might be beneficial for both partners through a series of enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial mycophagy has also been described in different environments (Leveau and Preston, 2008). Under controlled conditions, some bacterial strains have been proven capable of promoting (Kamei et al, 2012;Bontemps et al, 2013) or inhibiting (Radtke et al, 1994) the growth of white-rot fungi. More specifically, from a functional point of view, it has been suggested that bacterial-fungal interactions during the wood decay process might be beneficial for both partners through a series of enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the colonizing of vegetative structures of fungi by bacteria is used as a mechanism for a move to novel microhabitats and to occupy new niches [10]. Another study has shown that coexisting bacteria living with wood-decaying basidiomycetes significantly promoted the mycelial growth of its fungal host by mechanisms unclear until now [11]. Moreover, Pseudomonas species can interact with fungi and fungi-like organisms in plants directly.…”
mentioning
confidence: 99%
“…It is well known that many fungal species are involved in the degradation of wood. More recently it has been recognized that bacteria might collaboratively work with fungal species to accelerate wood decay [50]. Emerging molecular techniques are expanding our knowledge of the diversity of wood inhabiting organisms [51, 52].…”
Section: Resultsmentioning
confidence: 99%